Opening Opportunities for Fairness in Developing Alternative Sanctions for Corporations in Corruption Cases - Nani Arianti; Mispansyah Mispansyah; Suprapto Suprapto (International Journal of Sociology and Law, 2025)
Corporate corruption poses a significant threat to economic stability and public trust. Traditional punitive sanctions, such as substantial fines or dissolution, often fail to achieve restorative justice and can lead to unintended consequences, including harm to innocent employees and stakeholders. This paper explores the imperative of developing alternative sanctions for corporations implicated in corruption cases, with a central focus on establishing a framework grounded in fairness. Through a normative juridical research method employing statutory, comparative, and conceptual approaches, this study analyzes the limitations of the current punitive paradigm. It examines various alternative sanctions, including Deferred Prosecution Agreements (DPAs), Non-Prosecution Agreements (NPAs), corporate monitorship, and mandatory compliance program overhauls. The findings indicate that these alternatives offer a more flexible and effective mechanism for balancing accountability with corporate rehabilitation. They create opportunities to incentivize self-reporting, cooperation, and genuine internal reform. This paper concludes that by integrating principles of proportionality, restorative justice, and forward-looking prevention into the legal framework, a fairer and more effective corporate sanctioning system can be developed. Such a system would not only penalize misconduct but also foster a culture of corporate integrity and contribute more effectively to the broader fight against corruption.